The Next Iranian Revolution: Turning Challenges into Opportunities - Marsili, M. (I. International Congress of Iranian Studies (Iranian Congress), 2023)
About 45 years after the 1979 revolution which overthrew the last Shah, Mohammad Reza Pahlavi, the Islamic Republic of Iran became a regional power, thanks to four decades of social, economic, diplomatic, and military advancements. But not all of these successes are clear-cut. Many of Iran’s achievements created new challenges or even led to political and diplomatic failures. Some episodes isolated Iran and made dialogue with the West difficult: the takeover of the U.S. Embassy in Tehran in 1979, the military and financial support to Syria, Iraq, and Lebanon (Hezbollah), the adversarial relationship with Saudi Arabia, the anti-American, anti- Israeli, and anti-Semitic posture, and the controversial nuclear program, have alienated the sympathy of Western powers. The Islamic Republic has survived, despite sustained acute enmity from the US and Israel, a decade-long war against Iraq (1980-1988), and four decades of various forms of economic sanctions but, so far, was not able to come up with a governing model that reconciles the vision of a religious state with democracy. One of the last contemporary theocracies, along with Saudi Arabia and the Vatican, Iran should strive to introduce reforms, which are strongly demanded by the people: ease censorship, progress with human rights and respect for gender equality, restrict state intervention in the economy and pass electoral reforms. The harsh crack-down by the Islamic Revolutionary Guard Corps on anti-government protests which have broken out since 2017 demanding reforms or the end to the Islamic Republic have raised public outrage. After the U.S. withdrawal from the Joint Comprehensive Plan of Action in 2018, and the civil unrest against the government associated with the death of Mahsa Amini while in the custody of the Guidance Patrol, Iran's image has further deteriorated. After 20 years, Iran is still perceived as President George W. Bush characterized it, jointly with North Korea and Iraq, in his State of the Union address of January 29, 2002: ‘an axis of evil, arming to threaten the peace of the world’. Economic sanctions, such as the embargo against crude oil, have injured the Iranian economy which suffers from double- digit unemployment and high inflation. Iran country would enormously benefit from their removal and the openness to the global market, in compliance with Art. 12 of the Constitution which sets the regime's goals: ‘A fair economy based on Islamic criteria to create welfare and eliminate poverty and deprivation in the areas of nutrition, housing, employment, health and insurance’. Is the Tehran leadership able to get the country out of this long-term situation and bring it into a new era of prosperity? This work aims to analyze the current situation in Iran and the opportunities for the country to find the right place within the international society.